Mrs. Cockle's cat - "Pearce, Philippa" (Puffin: London, 1988)
Mrs Cockle's cat, Peter, is cross and miserable from staying indoors. Even worse, there is no fresh fish to eat. The weather is so bad that the fisherman can't take their boats out to sea. Finally, Peter can stand it no longer and goes in search of fish, leaving poor Mrs Cockle all alone.
Keywords: Cats Juvenile fiction